Application of fuzzy logic concept to profitability quantification in plastic recycling (2006)
This paper aims at applying a fuzzy logic control model to profitability in a case study of the plastic recycling industry in Nigeria. The studies of profitability components of the plastic recycling industry as used to develop a model framework and the application of fuzzy logic control model to the framework are given in this paper. A brief introduction to profitability concepts as well as useful suggestions and conclusions are all integral part of this paper which is based on the application of a fuzzy logic model of control to profitability concept in plastic recycling industry.